Implementation of Non-Destructive Radiographic Testing for Welding Defect Inspection on Heat Exchanger Project DXXXX at PT XYZ - Ismawaty, Marizka Putri; Herwanto, Dene; Sumitra, Naufal Rabbani; Sulaeman, Benyamine (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Welding in the heat exchanger fabrication process is a critical stage that determines structural integrity and operational safety, but internal defects are still often found that cannot be detected visually. This study was conducted to identify the type of welding defect in the Heat Exchanger Project DXXXX and analyze the causative factors based on ASME Section V and VIII standards. The research approach uses a descriptive qualitative method through direct observation of the welding process, Radiography Test documentation, and interviews with Quality Control personnel during field work practice activities. The results showed that out of 279 radiographic films examined at 29 connection points, 31 defects were found consisting of two main types, namely slag inclusion and porosity. Slag inclusion defects are the most dominant finding and are influenced by human factors and work methods, while porosity defects are mainly caused by inaccuracies in methods related to the regulation and use of shielding gas. These findings indicate that inconsistencies in welding procedures, suboptimal material preparation, and inconsistent process control contribute significantly to the occurrence of defects. This study concludes that the Radiography Test is able to provide a comprehensive picture of the quality of weld joints and the defect patterns that occur in heat exchanger fabrication. Recommendations include improving operator competence, reviewing welding procedures according to ASME standards, improving QC supervision, and regular calibration of welding equipment to minimize the recurrence of defects in the welding process in the future